2019
DOI: 10.1187/cbe.18-11-0227
|View full text |Cite|
|
Sign up to set email alerts
|

Mixed Student Ideas about Mechanisms of Human Weight Loss

Abstract: Recent calls for college biology education reform have identified “pathways and transformations of matter and energy” as a big idea in biology crucial for students to learn. Previous work has been conducted on how college students think about such matter-transforming processes; however, little research has investigated how students connect these ideas. Here, we probe student thinking about matter transformations in the familiar context of human weight loss. Our analysis of 1192 student constructed responses re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 25 publications
(64 reference statements)
3
41
0
Order By: Relevance
“…For our study, since we began with a holistic coding rubric aligned to the levels of the LP, we spent additional time developing and applying the set of analytic coding rubrics. Because the analytic bins are meant to identify conceptual pieces relevant to the specific item and levels, we developed a procedure to guide the process of creating these rubrics (Doherty et al 2019;Haudek et al 2019;Jescovitch et al 2019aJescovitch et al , 2019bScott et al 2019;Sripathi et al 2019). Therefore, the analytic coding rubrics in our study were unique to each item, although other reports have found such conceptual rubrics may hold across items in similar contexts (Moharreri et al 2014;Weston et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For our study, since we began with a holistic coding rubric aligned to the levels of the LP, we spent additional time developing and applying the set of analytic coding rubrics. Because the analytic bins are meant to identify conceptual pieces relevant to the specific item and levels, we developed a procedure to guide the process of creating these rubrics (Doherty et al 2019;Haudek et al 2019;Jescovitch et al 2019aJescovitch et al , 2019bScott et al 2019;Sripathi et al 2019). Therefore, the analytic coding rubrics in our study were unique to each item, although other reports have found such conceptual rubrics may hold across items in similar contexts (Moharreri et al 2014;Weston et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Various automated scoring tools and approaches have been developed for evaluation of student CR in science, over a range of grade levels and topics (Liu et al 2016;Mitchell et al 2002;Mayfield and Penstein-Rose 2010;Nehm and Haertig 2012;Sieke et al 2019;Sripathi et al 2019). For example, automated scoring systems have been applied to conceptual assessments aligned with key disciplinary ideas in undergraduate biology Sieke et al 2019).…”
Section: Machine Learning Of Constructed Response Assessmentsmentioning
confidence: 99%
“…We developed three analytic rubrics, one for each question (namely replication, transcription, and translation) using an approach of emergent coding and expert review, that our group has used successfully for similar work. 30 Some of the ideas targeted by our rubrics were originally identified via lexical analysis, which groups and quantifies words and phrases in text. 14 In contrast to lexical analysis, categorization with an analytic rubric uses words and phrases in context of the entire response.…”
Section: Rubric Development and Refinementmentioning
confidence: 99%
“…Responses to CR questions are thought to better diagnose student misconceptions and can contain mixtures of normative and nonnormative ideas. 26,27,29,30 Studies on CR instruments demonstrate that they are capable of eliciting key concepts and misconceptions and that student verbal responses in an interview closely match written responses. 27,31 Including CR items in assessment instruments can provide instructors with an opportunity to more accurately assess student conceptual understanding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation